Associations between changes in physical activity and perceived social exclusion and loneliness within middle-aged adults - longitudinal evidence from the German ageing survey - Linda Baumbach; Hans-Helmut König; André Hajek (BMC, 2023)
Abstract Background Previous research showed negative associations between physical activity and loneliness in older adults. However, information on associations among middle-aged adults is scarce. In this prognostic factor study, we investigated if starting or stopping to follow the WHO physical activity recommendations was associated with changes in perceived social exclusion and loneliness in this age bracket. Methods We used longitudinal representative data of participants aged 40 to 64 years from the German Ageing Survey waves in 2014 and 2017 (analytical sample = 4,264 observations, 54% women). Perceived social exclusion was investigated with the scale from Bude and Lantermann. Loneliness was quantified with the 6-items loneliness scale from De Jong Gierveld. Information from the International Physical Activity Survey items on the time spend in moderate and vigorous physical activity per week was dichotomized. Participants were coded as either following or not following the WHO´s physical activity recommendations of spending at least 150 min of moderate, 75 min of vigorous or an appropriated combination of physical activity per week. We investigated the within (individual) association between starting and stopping to follow WHO´s physical activity recommendations and perceived social exclusion as well as loneliness in asymmetric fixed effects regressions. Analyses were adjusted for age, marital status, employment status, social-network size, general self-efficacy, depressive symptoms, self-rated health, BMI, comorbidities, and physical functioning (SF-36). Results Stopping to follow the physical activity recommendations from the WHO was associated with perceived social exclusion (ß= 0.09 p = 0.04) but not with loneliness (ß=-0.01, p = 0.71). Starting to follow the WHO physical activity recommendations was neither associated with social exclusion (ß=-0.02, p = 0.54) nor with loneliness (ß=-0.01, p = 0.74) in adjusted asymmetric fixed effects regressions. Conclusion In middle-aged adults, longitudinal associations were found for physical activity and perceived social exclusion. Perceived social exclusion may be prevented by maintaining at least 150 min of moderate physical activities per week, which is the WHO physical activity recommendation. Future research should investigate moderators and mediators in the association between physical activity and social exclusion as well as loneliness.